Overcoming Sleep Disorders with Complementary Therapy for Patients Undergoing Hemodialisis - Rasmiati, Rasmiati; Herawati, Tuti; Sukmarini, Lestari (JOSING: Journal of Nursing and Health, 2024)
This study aims to collect relevant information on the effectiveness of complementary therapies in treating sleep disturbances in patients undergoing routine hemodialysis. The method used in this study is a literature study by collecting and reviewing several published articles regarding the role, use, and effect of complementary therapy in patients on routine hemodialysis with sleep disturbance problems. The results showed the effectiveness of complementary therapies such as music therapy, acupressure, and Benson's relaxation in overcoming sleep disturbances and improving patients' sleep quality. In conclusion, the three complementary therapies can overcome sleep disturbances and improve hemodialysis patients' sleep quality. However, of the three therapies, the authors concluded that Benson's relaxation intervention was an intervention that had better effectiveness than other complementary therapies. Keywords: Complementary Therapy, Hemodialysis, Sleep Disorders